Research of different adjuvants and yeast dosages in honey fermentation process - Sarba, Cristina; Timar, Adrian; Mărghitaş, Alexandru (Acta Agraria Debreceniensis, 2016)
In order to ferment honey it is necessary to add in the fermentation environment some substances with the role of adjuvants, to improve the honey must composition and to help the fermentation process. There were tested 2 different combination of adjuvants which were analyzed in the fermentation process. Also the physical and chemical properties of the final products were analyzed. After establishing the most suitable mix of adjuvants it was necessary to test the right dosage of the yeast used to metabolized sugars: Saccharomyces cerevisiae, in order to obtain appropriate organoleptic properties.